MOVPE growth of AlxGa1‐xN with x ∼ 0.5 on epitaxial laterally overgrown AlN/sapphire templates for UV‐LEDs. Issue 3 (22nd January 2014) - Knauer, A.; Zeimer, U.; Kueller, V.; Weyers, M.
Abstract: The crystalline perfection of Alx Ga1‐x N layers with Al content of x ∼ 0.5 on epitaxial laterally overgrown (ELO) AlN with low defect density was investigated by spatially and spectrally resolved cathodoluminescence, scanning electron and atomic force microscopy. Cathodoluminescence mapping reveals compositional variations caused by different Ga incorporation during growth over macro‐steps resulting from step bunching on the ELO‐AlN. Introducing AlN interlayers as marker the influence of the macrosteps as well as of the growth rate on the development of Ga‐rich regions was studied. With increasing growth rate from 0.2 to 1 µm/h the spatial extension of the Ga‐rich regions is strongly reduced. At the same time the difference in Ga content is increased. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)